100 UMP Kilau volunteers continue to serve together with the community of Kampung Tammalang - Rozana, Sahadan (2023)
TAMMALANG, THAILAND, 3 July 2023 - Universiti Malaysia Pahang (UMP) Kilau volunteers, consisting of students and staff, once again dedicated themselves to the land of Tammalang to carry out community service activities together with the community and volunteering.